Challenge-Based Learning in Probability: Developing Digital Teaching Materials for High School Students - Arifia, Adhelia Putri; Jumroh, Jumroh; Lusiana, Lusiana; Vucelja, Stevan (FKIP Universitas Lampung, 2025)
This study aims to develop digital teaching materials on probability using the Challenge-Based Learning (CBL) model that meets the criteria of being valid, practical, and potentially effective. This is motivated by the low level of difficulty students face in understanding abstract probability material and the lack of interesting and effective learning resources. The development of these teaching materials is expected to provide an innovative solution to overcome the limitations of existing learning resources, particularly in mathematics learning, such as those related to probability. The research used a Research and Development (R&D) approach following the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Instruments used included expert validation questionnaires, student learning outcome tests, and student response questionnaires. This research trial was conducted on class X students of SMA Negeri 4 Palembang. Data were analyzed both descriptively and quantitatively to assess the quality and impact of the developed materials. The validation results show that the digital teaching materials fall into the “highly valid” category with an average score of 88.66%. The practicality assessment based on student response questionnaires obtained an average score of 89.67% and was categorized as “highly practical”. Data collection on learning outcomes was conducted through pretest and posttest learning assessments. Data analysis included normality tests, N-Gain tests to determine the extent of learning improvement, and paired t-tests to determine the significance of differences. The t-test results yielded a Sig. (2-tailed) value of 0.000 less than 0.05, indicating a significant difference between the pretest and posttest scores. The N-Gain test yielded a value of 0.77, categorized as high. The developed product not only meets quantitative criteria but also contributes pedagogically by increasing students' active engagement in the learning process. The integration of the CBL model and digital media enhances students' motivation, participation, and understanding of abstract mathematical concepts. By utilizing Flip PDF software, teaching materials are converted into interactive e-book formats that are more engaging and accessible. This product is worthy of broader application in mathematics education at the high school level. Keywords: digital teaching materials, challenge-based learning, flip PDF professional, probability.